Purification and characterization of a serine protease from Cucumis trigonus Roxburghi - Asif-Ullah, Mufti; Kim, Key-Sun; Yu, Yeon Gyu (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
Kachri fruit, Cucumis trigonus Roxburghi, contains high protease activity and has been used as meat tenderizer in the Indian subcontinent. A 67 kDa serine protease from Kachri fruit was purified by DEAE-Sepharose and CM-Sepharose chromatography, whose optimum activity was at pH 11 and 70 degrees C. Its activity was strongly inhibited by PMSF, but not by EDTA, pepstatin, or cysteine protease inhibitors. The substrate specificity of the purified protease towards synthetic peptides was comparable to cucumisin, the first characterized subtilisin class plant protease from the sarcocarp of melon fruit (Cucumis melo). These characteristics, along with the N-terminal amino acid sequence, indicated that the isolated protease from Cucumis trigonus Roxburghi is a cucumisin homologue, which belongs to the serine protease family. (c) 2006 Elsevier Ltd. All rights reserved.